The Norbornadiene/Quadricyclane Pair as Molecular Solar Thermal Energy Storage System: Surface Science Investigations - Hemauer, Felix; Steinrück, Hans-Peter; Papp, Christian (ChemPhysChem, 2024)
For the transition to renewable energy sources, novel energy storage materials are more important than ever. This review addresses so-called molecular solar thermal (MOST) systems, which appear very promising since they combine light harvesting and energy storing in one-photon one-molecule processes. The focus is on norbornadiene (NBD), a particularly interesting candidate, which is converted to the strained valence isomer quadricyclane (QC) upon irradiation. The stored energy can be released on demand. The energy-releasing cycloreversion from QC to NBD can be initiated by a thermal, catalytic, or electrochemical trigger. The reversibility of the energy storage and release cycles determines the general practicality of a MOST system. In the search for derivatives, which enable large-scale applications, fundamental surface science studies help to assess the feasibility of potential substituted NBD/QC couples. We include investigations under well-defined ultra-high vacuum (UHV) conditions as well as experiments in liquid phase. Next to the influence of the catalytically active surfaces on the isomerization between the two valence isomers, information on adsorption geometries, thermal stability limits, and reaction pathways of the respective molecules are discussed. Moreover, laboratory-scaled test devices demonstrate the proof of concept in various areas of application.
CRIS-Team Scopus Importer:2024-03-15
Keywords: energy storage; heterogeneous catalysis; MOST systems; norbornadiene; surface science